2017
DOI: 10.1111/aab.12339
|View full text |Cite
|
Sign up to set email alerts
|

Fertiliser application positively affects plants performance but reduces seed viability in seashore mallow (Kosteletzkya pentacarpos): implication for biomass production and species conservation

Abstract: Kosteletzkya pentacarpos (L.) Ledeb. (seashore mallow) is recognized as an important plant species for several industrial applications, especially in North America and Asia. In Europe, seashore mallow is highly threatened and subject of conservation actions (e.g. reintroduction). In order to define appropriate multipurpose cultivation protocols, suitable for biomass production and for conservation purposes, we investigated the effect of varying levels of soil salt content and nutrient availability on seashore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It has been reported that there is a trade-off between number and size of seeds, which enable plants to adapt and survive in their varied habitat (Gan et al 2013). Abeli et al (2017) reported that under stressful environment plants invest more photosynthates towards reproduction and enhance the provisioning and quality of seeds as an adaptive response to ensure survival of seedlings. This might be happened in our case, where the number of seeds reduced while seeds size and mass did not show any signi cant variation as an adaptive response under stressful environment of UV-B.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is a trade-off between number and size of seeds, which enable plants to adapt and survive in their varied habitat (Gan et al 2013). Abeli et al (2017) reported that under stressful environment plants invest more photosynthates towards reproduction and enhance the provisioning and quality of seeds as an adaptive response to ensure survival of seedlings. This might be happened in our case, where the number of seeds reduced while seeds size and mass did not show any signi cant variation as an adaptive response under stressful environment of UV-B.…”
Section: Discussionmentioning
confidence: 99%
“…A previous experiment showed that fertilized seashore mallow plants produced low‐quality seeds, suggesting that there is a trade‐off between maternal plant vigour and the quality of the offspring (Abeli et al, ). This behaviour was attributed to different seed provisioning by maternal plants under various levels of stress, via maternal effects (Galloway & Etterson, ; Kochanek, Steadman, Probert, & Adkins, ), and was at the core of our second question.…”
Section: Discussionmentioning
confidence: 99%
“…Seashore mallow plants from two generations (maternal plants and offspring) were used for the translocation experiment in 2015. The year before, the maternal plants had been cultivated in the Botanical Garden of the University of Ferrara with a factorial combination of three levels of salt addition [none (0S), low (LS), and high (HS) additions of salt] and three levels of fertilizer addition [none (0F), low (LF) and high (HF) levels of fertilizer added]; see Abeli et al () for further information. The offspring plants were germinated from seeds collected from maternal plants, but received no further treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation